2013
DOI: 10.1128/jvi.02118-12
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Impact of Host and Viral Factors on HIV-1 Viral-Load Control during Early Infection

Abstract: fIn HIV-1 infection, the early set-point viral load strongly predicts both viral transmission and disease progression. The factors responsible for the wide spectrum of set-point viral loads are complex and likely reflect an interplay between the transmitted virus and genetically defined factors in both the transmitting source partner and the seroconverter. Indeed, analysis of 195 transmission pairs from Lusaka, Zambia, revealed that the viral loads in transmitting source partners contributed only ϳ2% of the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
48
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 55 publications
(83 reference statements)
6
48
1
Order By: Relevance
“…Analogous to the negative effects of transmitted drug resistance on treatment efficacy (23), acquisition of HIV-1 "preadapted" to (i.e., harboring escape mutations specific for) an individual's HLA alleles could compromise cellular immune responses to the incoming virus. This is supported by the observation that individuals infected with HIV-1 harboring polymorphisms associated with HLA alleles they share with their donors (their mothers in the case of vertical trans-mission or partners in the case of horizontal transmission) display suboptimal CTL responses and/or adverse clinical outcomes (19,(24)(25)(26)(27).…”
Section: H Uman Leukocyte Antigen (Hla) Class I-restricted Cd8mentioning
confidence: 55%
“…Analogous to the negative effects of transmitted drug resistance on treatment efficacy (23), acquisition of HIV-1 "preadapted" to (i.e., harboring escape mutations specific for) an individual's HLA alleles could compromise cellular immune responses to the incoming virus. This is supported by the observation that individuals infected with HIV-1 harboring polymorphisms associated with HLA alleles they share with their donors (their mothers in the case of vertical trans-mission or partners in the case of horizontal transmission) display suboptimal CTL responses and/or adverse clinical outcomes (19,(24)(25)(26)(27).…”
Section: H Uman Leukocyte Antigen (Hla) Class I-restricted Cd8mentioning
confidence: 55%
“…Previously, our work, and that of others, showed that transmitted viral characteristics significantly correlate with early SPVL (11,13,14) as well as CD4 + T-cell decline up to 3 y postinfection (15). Here, we sought to determine the underlying mechanisms by which vRC of transmitted HIV-1 impacts the trajectory of CD4 decline even in the context of viral control by previously identified host factors, such as protective HLA alleles, that also impact disease progression.…”
Section: Resultsmentioning
confidence: 99%
“…The observation that not all individuals harboring such protective HLA class I alleles go on to become long-term nonprogressors suggests that other factors outside of host immunogenetics play a role in defining disease progression (12). Transmitted viral characteristics have been shown to impact viral load within heterosexual transmission pairs, suggesting that viral characteristics are heritable and can impact disease severity (11,13,14). Moreover, we recently showed that attenuated viral replicative capacity (vRC) of the transmitted virus, defined in vitro by the Gag sequence, was associated with a significant delay in CD4 + T-cell decline in individuals recently infected with HIV-1 subtype C (15).…”
mentioning
confidence: 99%
“…Additionally, in this model, HLA concordance within transmission pairs and TLR SNPs of the seroconverter also were associated with changes in set point. In a previous study of Zambian HIV-1 serodiscordant couples, male sex, age, HLA alleles, HLA concordance, and source partner HIV-1 RNA level explained ϳ37% of the variation in set point (9). The increased variation explained by our current model may be partly attributed to variation in the TLR genes, which previously have been shown to be associated with innate host control of HIV-1 (30, 32-39).…”
Section: Discussionmentioning
confidence: 53%
“…This HIV-1 set point level is a critical determinant of later disease progression and infectivity (1)(2)(3)(4) and is thought to be a measure of the balance between the replicative fitness of the transmitted virus and the antiviral responses of the new host. The importance of viral characteristics in determining set point is supported by multiple studies reporting a strong correlation between plasma HIV-1 RNA levels in HIV-1-transmitting (source) partners with the HIV-1 set point of their seroconverting partner (5)(6)(7)(8)(9)(10). The host contribution is exemplified by the importance of variation in the human leukocyte antigen (HLA) class I (HLA-A, HLA-B, and HLA-C) genes, which are strongly associated with set point by virtue of the essential role for HLA in presenting HIV-1 peptides to CD8 ϩ T cells (11).…”
mentioning
confidence: 77%